Pelatihan Pengelolaan Keuangan Digital bagi Pelaku UMKM di Wilayah Cikarang (Neolectura, 2022)
As an entrepreneur, MSME actors certainly need sales records that describing overall their business that they manage well and efficiently. Many businesses are having difficulties to grow up because of the problem of untidy records or even not being recorded at all. Digital financial management is one of the trainings for beginner digipreneurs in order to prepare tough entrepreneurs to increase their business income, manage finances and access funds by utilizing technology. Participants of the Digital Entrepreneurship Academy Training – Beginner Class will learn about managing business finances using applications, how to get capital to expand a business, market products digitally through integrated electronic transaction services that are devoted to improving the welfare of MSME actors on an ongoing basis through digital transaction services that can answer various administrative and financial problems in the MSME ecosystem. The training is carried out offline at a predetermined location from March – July 2022, divided into several waves, the waves are carried out for 2 days with a training duration of 13 JP. In this training, participants get 6 materials in theory and practice which have been prepared by Community Service Partners, BPPTIK RI.